THE RELATIONSHIP BETWEEN FRACTURED TECTONIC AND GROUNDWATER RESERVOIR OF MASSIVE FORMATIONS OF OSSA MOUNTAIN (E. THESSALY, GREECE) - Σταμάτης, Γ.; Μιγκίρος, Γ. (Bulletin of the Geological Society of Greece, 2004)
Ossa mountain is an area of great hydrogeological interest due to its geological structure. In this Paper the massive lithological formations and the tectonic structure are presented in relation to the forming of Ossa hydrogeological conditions. The groundwater flow directions are directly depended on the dominant anticline structure of Ossa mountain. The observing of field measurements as well as the processing of aerial photos reviled some transversal zones of high fracture. A great amount of groundwater is moving through some main zones of NNE direction as well as some secondary zones of N-S and E-W directions. A direct relationship is shown between tectonical structures and springs. The hydrochemical character of aquifers are presented through chemical analysis. Specifically, the detected Ca-HC03 reveals waters from karstic formations, while Ca-Mg-HC03, Ca-Mg-Na-HC03 reveals origins from metamorphic formations.